2021
DOI: 10.1111/jocd.14177
|View full text |Cite
|
Sign up to set email alerts
|

Is there a rationale for the use of botulinum toxin in the treatment of Androgenetic Alopecia?

Abstract: How to cite this article: Melo DF, Ramos PM, Antelo DA, Machado CJ, Barcaui CB. Is there a rationale for the use of botulinum toxin in the treatment of Androgenetic Alopecia?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Alopecia areata, androgenetic alopecia, cephalalgic alopecia and radiation-induced alopecia have all been treated with BoNT-A1 (Cutrer et al 2010 ; Zhou et al 2020 ; Melo et al 2021 ). Blood flow is a primary determinant in follicular health and although the exact mechanism by which BoNT aids hair regrowth is uncertain, it has been proposed that BoNT-A1 injected into the scalp would decrease microvascular pressure by relaxing muscles thus improving oxygen supply to hair follicles (Melo et al 2021 ). Although most studies show a clinical improvement in density or growth of hair and high patient satisfaction, further randomized clinical trials are necessary to determine the real effect of BoNT on hair growth.…”
Section: Novel Therapeutic Applications Of Botulinum Neurotoxinsmentioning
confidence: 99%
“…Alopecia areata, androgenetic alopecia, cephalalgic alopecia and radiation-induced alopecia have all been treated with BoNT-A1 (Cutrer et al 2010 ; Zhou et al 2020 ; Melo et al 2021 ). Blood flow is a primary determinant in follicular health and although the exact mechanism by which BoNT aids hair regrowth is uncertain, it has been proposed that BoNT-A1 injected into the scalp would decrease microvascular pressure by relaxing muscles thus improving oxygen supply to hair follicles (Melo et al 2021 ). Although most studies show a clinical improvement in density or growth of hair and high patient satisfaction, further randomized clinical trials are necessary to determine the real effect of BoNT on hair growth.…”
Section: Novel Therapeutic Applications Of Botulinum Neurotoxinsmentioning
confidence: 99%
“…Another proposed mechanism of action is a vasodilating effect in scalp blood vessels that would help eliminate scalp DHT faster. 34 Although some studies have demonstrated reduction in AGA grading scales with statistical significance, 35,36 a recent systematic review states that there is still no evidence to recommend the inclusion of botulinum toxin in our therapeutic approach to AGA. 37 Low-level light therapy (LLLT) LLLT devices are used in a variety of dermatological conditions due to their biomodulatory effects which include anti-inflammatory and immunomodulatory activity, and improvement of local blood flow through a diverse range of wavelengths.…”
Section: Botulinum Toxinmentioning
confidence: 99%
“…Another proposed mechanism of action is a vasodilating effect in scalp blood vessels that would help eliminate scalp DHT faster 34 . Although some studies have demonstrated reduction in AGA grading scales with statistical significance, 35,36 a recent systematic review states that there is still no evidence to recommend the inclusion of botulinum toxin in our therapeutic approach to AGA 37 …”
Section: Treatment Of Agamentioning
confidence: 99%
“…Botulinum toxin (BoNT) is a potent neuromodulator, that serves as a highly versatile drug, with numerous clinical applications for both therapeutic and aesthetic purposes. The evolving knowledge of the role of BoNT in inhibiting neurogenic inflammation, mainly by impeding nerve-derived release of CGRP and SP, has contributed to its 'off label' use for the management of various inflammatory skin disorders, including psoriasis, rosacea [10], atopic dermatitis [11], alopecia [12][13][14], and many other dermatological conditions [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…SP has also been proven to be an important mediator of the inflammatory response in a mouse model for alopecia areata [19]. The exact mechanisms behind the effect of BoNT in androgenetic alopecia are still uncertain, and it has been hypothesized that BoNT scalp injections generate local muscle relaxation, and consequently alleviate microvascular pressure and enhance oxygen supply to hair follicles [13]. BoNT has also been administrated as an effective adjuvant treatment for various conditions that affect the intertriginous areas, such as Hailey-Hailey disease [20,21], Darier disease [22], and hidradenitis suppurativa [23,24].…”
Section: Introductionmentioning
confidence: 99%